(untitled) (Al-Academy, 2017)
Find cares studying the aesthetics of environmental art, one of the topics that is one of the problems of the aesthetic side in the arts of postmodernism, so this research came as an attempt to get to know the aesthetic concepts of environmental art that can be learned from functional testing in the formation of the post-modern control. The research involved four chapters: The first chapter discusses the general framework of the research methodology, as it was displayed in itThe research problem and its importance and define its objective to identify the aesthetics of environmental art at the level of the body, meaning, the receiver .ozlk in Iraq and America as the spatial limits of the time limits are period stretching from 1970 to 2006, because of this period (1970) the beginning of documenting achievements environmental art. And ensure that the second chapter the theoretical framework through the first two sections dealt with concepts about environmental and ecological second intake was studying art and the most important and orientations and its nutrients aesthetic. While the third quarter included research procedures through the codification of the research community and appointed by the methodology, and then analyze the sample models and guestrooms) 3. (Models have been selected purposely, and taking into account the representation. The fourth chapter was devoted to the search results, the most important being: the meaning content form in postmodern art anchor dialectically in terms of reaction controversy relational between raw materials manufactured ready-made ones and natural to create a kind of coalition across the variation to create harmony harmonious in structural construction formative